ANALISIS RASIO PROFITABILITAS TERHADAP PENGUKURAN KINERJA KEUANGAN PADA PERUSAHAAN PT. UNILEVER TBK - Dian Febriana; Candra Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The aim of the research was to find out how effective profitability ratio analysis can be in assessing the financial performance of companies, such as Unilever Company, whether the financial performance of PT. Unilever Tbk is good or not good. The reason I conducted research on the Unilever company was because Unilever was a very good choice to research in the context of profitability ratios and company performance evaluation. As one of the world's leading consumer companies, Unilever has a strong brand portfolio and a significant global presence in the food, beverage and household industries. The data taken is official financial report information from the Unilever Company which is published and has been approved by the IDX. The method used in the research is to apply quantitative research. The data comes from measured data and processed by researchers from Unilever company financial report information for the period 2018 - 2022. So it can be seen from the Net Profit Ratio of 72%, Gross Profit Ratio of 51%, ROA of 35%, and ROE of 135%. These four ratios have exceeded the industry average ratio. This means that the Unilever company can maximize profits on sales, assets and equity. So, from the analysis of profitability ratios to the measurement of the company's financial performance, Unillever found good profitability.